No Effect of Interset Palm Cooling on Acute Bench Press Performance, Electromyography Amplitude, or Spectral Frequencies in Resistance-Trained Men. Issue 3 (2nd March 2023) - McMahon, Gerard; Kennedy, Rodney; Burden, Adrian
Abstract: McMahon, G, Kennedy, R, and Burden, A. No effect of interset palm cooling on acute bench press performance, electromyography amplitude or spectral frequencies in resistance-trained men. J Strength Cond Res 37(3): 555–563, 2023—Previous research has suggested that cooling distal to the working agonist muscles during the interset rest periods of high-intensity resistance exercise may facilitate improved performance through increased agonist activation. However, these studies have used inappropriate electromyography (EMG) normalization techniques. Therefore, the aim of this study was to compare 2 palm-cooling conditions with a thermoneutral condition during high-intensity resistance exercise and subsequent effects on exercise performance, EMG amplitude, and spectral frequencies using appropriate normalization methodologies. Eleven healthy, resistance-trained, young men (20–36 years old) performed 4 sets of bench press exercise to exhaustion at 80% 1RM each separated by 3 minutes of passive recovery. Palm-cooling (10° C [TEN] or 15° C [FTN]) or thermoneutral (28° C [CON]) conditions were applied for 60 seconds during the recovery interval of each set in a randomized, double-blind fashion, with 4 days of recovery between experimental conditions. Palm temperature was significantly lower ( p < 0.05) in the TEN and FTN conditions compared with CON. Number of repetitions and mean power in the bench press declined significantly after each set in all conditions ( p < 0.05). There were no significant differences ( p > 0.05) in any bench press performance or EMG-related variables between any of the conditions. Palm cooling at either 10 or 15° C had no effects on bench press performance compared with a thermoneutral condition, with no observable effects on neuromuscular responses during exercise. Therefore, cooling is not currently recommended as an ergogenic strategy to enhance acute bench press performance during high-intensity resistance training.